Strategi Menghadapi Persaingan Usaha: (Studi Kasus pada Laila MUA) - SUSANTI, AGUS (Prodi Administrasi Bisnis FISIP Universitas Tulang Bawang Lampung, 2024)
Businesses in the beauty sector are currently experiencing very rapid growth, giving rise to tight competition. Technological developments and social media influence people's needs and desires in the field of beauty. Situations like this require entrepreneurs in the beauty sector to have a strategy to face competition. Laila MUA has problems implementing effective strategies to face increasingly tight business competition. The aim of this research is to find out the strategies or methods used by Laila MUA in facing business competition. Provide recommendations for effective strategies for Laila MUA to increase their competitive ability in the beauty business. The research uses qualitative descriptive analysis. Data sources were obtained from primary data by conducting non-participant observation, unstructured direct interviews and documentation. Meanwhile, secondary data was obtained from literature that supports this research. The results show that Laila MUA needs to 1) Increase knowledge and skills. (2) Update portfolio (3) Live streaming, hold giveaways (4) Collaborate with other professionals (5) Improve service quality (6) Create packages and promotions (7) Increase use of digital technology (8) Sterilize make-up tools and products used (9) Additional services, before the ceremony or reception (10) Attending industry events, beauty exhibitions and professional meetings. Conclusion: Strategy recommendations include: Improving skills and knowledge, building an attractive portfolio, utilizing social media, collaborating with other professionals, improving customer service, creating packages and promotions, increasing reviews and testimonials, maintaining cleanliness and quality, offering additional services, build networks and reputation. Suggestions: develop innovation and creativity in products and services, digital technology and adapt to the changing business environment. Keywords: strategy, business competition, MUA